2003
DOI: 10.1093/hmg/ddg087
|View full text |Cite
|
Sign up to set email alerts
|

Non-syndromic vestibular disorder with otoconial agenesis in tilted/mergulhador mice caused by mutations in otopetrin 1

Abstract: Otoconia are biominerals within the utricle and saccule of the inner ear that are critical for the perception of gravity and linear acceleration. The classical mouse mutant tilted (tlt) and a new allele, mergulhador (mlh), are recessive mutations that affect balance by impairing otoconial morphogenesis without causing collateral deafness. The mechanisms governing otoconial biosynthesis are not known. Here we show that tlt and mlh are mutant alleles of a novel gene (Otopetrin 1, Otop1), encoding a multi-transme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
133
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(145 citation statements)
references
References 53 publications
11
133
1
Order By: Relevance
“…In contrast, others, such as stargazer (Khan et al 2004), het (Paffenholz et al 2004), isk (Vetter et al 1996), tlt and mlh (Hurle et al 2003), Pmca2 (Kozel et al 1998), shaker/waltzer (Sun 2001), and hscy (Longo-Guess et al 2005), have not been reported as having significant bony abnormalities. It is not known, however, if some of these animals may have relatively subtle changes in the anatomy of the temporal bone that have gone unnoticed.…”
Section: Introductionmentioning
confidence: 98%
“…In contrast, others, such as stargazer (Khan et al 2004), het (Paffenholz et al 2004), isk (Vetter et al 1996), tlt and mlh (Hurle et al 2003), Pmca2 (Kozel et al 1998), shaker/waltzer (Sun 2001), and hscy (Longo-Guess et al 2005), have not been reported as having significant bony abnormalities. It is not known, however, if some of these animals may have relatively subtle changes in the anatomy of the temporal bone that have gone unnoticed.…”
Section: Introductionmentioning
confidence: 98%
“…Similar to the phenotypes seen in het and hslt mice, the tilted (tlt), mergulhador (mlh), and inner ear defect (ied) mice carry mutations in the novel multi-transmembrane domain protein, Otopetrin 1 (Otop1), resulting in nonsyndromic otoconial agenesis and a severe balance disorder in mice (Besson et al, 2005;Hurle et al, 2003;Ornitz et al, 1998). The zebrafish otop1 orthologue is a highly conserved gene that is essential for otolith initiation as seen in both morphant otop1 fish and in the backstroke mutant (Hughes et al, 2004;Sollner et al, 2004).…”
Section: Locally Increase Calcium and Carbonate Concentrations To Inimentioning
confidence: 94%
“…het )], abbreviated het(+/−)] as well as confirmed homozygous tilted mice [(C57BL/6J-Otop1tlt)/(C57BL/6J-Otop1tlt), abbreviated tlt(−/−) (Hurle et al 2001(Hurle et al , 2003]; and heterozygous tilted (C57BL/6J)/(C57BL/6J-Otop1tlt), abbreviated tlt(+/−). The absence or presence of otoconia was confirmed postmortem in all animals by visual inspection of maculae under the dissecting microscope.…”
Section: Animals and Surgical Preparationmentioning
confidence: 96%
“…This would provide a means to evaluate the role, if any, for static loading in the generation of resting mean discharge rates and characteristics. The discovery of mouse mutations that lack macular otoconia suggests an opportunity to study unloaded macular receptors and primary afferents in detail (Bergstrom et al 1998;Hurle et al 2001Hurle et al , 2003Paffenholz et al 2004). …”
Section: Introductionmentioning
confidence: 99%